Discussion on the mechanism of HER2 resistance in esophagogastric junction and gastric cancer in the era of immunotherapy - Yan Zhang; Wenxuan Fan; Fei Su; Xiaoling Zhang; Yunyi Du; Weiling Li; Yangjun Gao; Wenqing Hu; Jun Zhao (Human Vaccines & Immunotherapeutics)
Human epidermal growth factor receptor 2 (HER2) is a critical biomarker and therapeutic target in gastric/gastroesophageal junction (G/GEJ) cancers, despite the initial success of HER2-targeted therapies, such as trastuzumab, resistance to these drugs has emerged as a major impediment to effective long-term treatment. This review examines the mechanisms of drug resistance in HER2-positive G/GEJ cancer, the primary mechanisms of resistance explored include alterations in the HER2 receptor itself, such as mutations and changes in expression levels, as well as downstream signaling pathways, and interactions with the tumor microenvironment (TME). Furthermore, the review discusses the Novel therapeutic approaches, including the use of antibody-drug conjugates (ADCs) and combination therapies are assessed for their potential to enhance outcomes. By integrating recent research findings and clinical trials, this review aims to provide oncologists and researchers with insights into developing more effective treatments for patients with drug-resistant HER2-positive G/GEJ cancer.